2013
DOI: 10.1097/brs.0b013e318294835b
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Patients With Symptomatic Metastatic Spinal Cord Compression

Abstract: Patients with MSCC from pulmonary and renal cancers experienced improved survival in the study period. No improvement was seen for patients with other oncological diagnoses. This corresponds to reports from oncological studies and could affect preoperative scoring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…This population corresponded to 28 % of our global population, underlining the potential positive evolution of the prognosis for MSCC patients. Recent reports have suggested a potential improvement in this prognosis, mainly for patients with lung or renal cancer [5], and such improvements could be explained by the refinement of surgical techniques, and by the improvement in the use of systemic therapy for these two tumor types [13,14]. In our series, breast cancer and hematological primaries, both known to display a high sensitivity to systemic treatments, represented more than 80 % of the long-term survival patients.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This population corresponded to 28 % of our global population, underlining the potential positive evolution of the prognosis for MSCC patients. Recent reports have suggested a potential improvement in this prognosis, mainly for patients with lung or renal cancer [5], and such improvements could be explained by the refinement of surgical techniques, and by the improvement in the use of systemic therapy for these two tumor types [13,14]. In our series, breast cancer and hematological primaries, both known to display a high sensitivity to systemic treatments, represented more than 80 % of the long-term survival patients.…”
Section: Discussionmentioning
confidence: 91%
“…However, these scores were redundant and their validities were not confirmed [10,11], underlining the remaining crucial role of the use of multidisciplinary consultation. Simultaneously, long-term survival of MSCC patients has been suggested to increase, but to date no clear data have been reported on this issue [5]. Rades et al [12] evaluated patients surviving more than 1 year, but this analysis concerned only patients treated with conventional radiotherapy.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Rades et al [32,33] studied 356 cases of MSCC secondary to NSCLC between 1992 and 2010 and described survival times of 6 and 12 months at 28% and 14%, respectively; the median survival time was 4 months. Yet, Morgen et al [34] demonstrated that the survival time of 12 months in patients with MSCC secondary to LC revealed a statistically significant increase between 2005 and 2010, ranging from 4% to 19%. These recent results revealed an improvement in the prognosis of this population.…”
Section: Discussionmentioning
confidence: 95%